Sistem Pendukung Keputusan Metode Probabilistic Untuk Pinjaman KUR di Bank BRI Aek Nabara - Juniardi, Rizki; Adawiyah, Robiatul (Buletin Ilmiah Informatika Teknologi, 2025)
Credit is a form of financing for most economic activities. Credit is an important activity for cooperatives, because credit is one source of funds for cooperatives. Before starting credit granting activities, a good and thorough analysis of all aspects of credit that can support the credit granting process is required, in order to prevent the emergence of credit risks and the emergence of irregularities, one of which is bad credit. Therefore, it is necessary to have a system that can support decision making in providing credit. With the decision support system created, it is hoped that it can help the cooperative chairman in analyzing credit and reducing the level of bad credit in the cooperative. For the Probabilitic method there are 3 highest alternatives, namely in the first place with the name Pratiwi Amalia getting a value of 0.604, second place with the name Helmi Yanti getting a value of 0.475, third place with the name Cut Arpiah Hasibuan getting a value of 0.439